PELAKSANAAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 DALAM PEDEMI COVID-19 TEHADAP JUAL BELI GAS LPG 3 KG MENURUT SYARIAH DI KECAMATAN BENGKALIS - Utari, Yuni Dhea; Ilham, Muhammad (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The implementation of Law Number 8 of 1999 concerning consumer protection for selling and purchasing 3 kg LPG gas in the Bengkalis sub-district has yet to be protected. The business actors themselves do not know consumer protection laws. Many problems arise because of business actors, one of them business actors reducing the volume of LPG gas by 3 kg. Constraints in implementing consumer protection for buying and selling gas in the Bengkalis sub-district are caused by several obstacles. Consumers often have difficulty getting 3 kg LPG gas, significantly when fuel prices increase. This means that there are still many problems that occur in the field. Consumers also complain because so many get LPG gas and the tube volume is only half of the tube. There is no guarantee given to these consumers. Still, business actors admit that there needs to be more socialization by the government to the public so that the public is not aware of consumer protection laws, guarantees, and rights. The enactment of written law still makes rights as consumers not well realized. There are still many consumers who feel they are living in injustice committed by business actors to sell their wares because many business actors are looking to take advantage of the rights that these consumers should have